Damage constitutive model and experimental study of deep coal rock under thermal-hydro-mechanical coupling - Kunhong Lv; Hui Zhang; Baokang Wu; Boyuan Yang; Yuting Zhou; Xingyu Li; Xu Luo; Jintao An (Scientific Reports)
Abstract This study investigates the thermal-hydro-mechanical (THM) coupled damage behavior of deep coal rocks from the Benxi Formation in the Ordos Basin. By conceptualizing coal rock as a dual-porosity medium comprising fractures and matrix, a damage constitutive model was developed through the integration of the Lemaitre strain equivalence hypothesis, continuum damage mechanics, and thermodynamic principles. The model introduces damage variables and correction coefficients to characterize the synergistic effects of confining pressure, temperature, and drilling fluid infiltration. Experimental validation was performed using a custom-designed multi-field coupled triaxial testing system, with triaxial compression tests conducted across varying confining pressures, temperatures, and moisture content conditions. The results show that: (1)The proposed constitutive model successfully quantifies damage evolution under HTM coupling, where parameter q governs residual deformation characteristics and parameter n modulates post-peak stress degradation trends; (2)Drilling fluid immersion induces time-dependent mechanical deterioration, significantly reducing peak stress and elastic modulus, with increasing moisture content exacerbating nonlinear degradation effects; (3)Macroscopic failure modes transition from tensile-shear conjugate patterns to single shear planes as confining pressure decreases and moisture content increases; (4)Theoretical stress-strain curves demonstrate strong consistency with experimental data, validating the model’s capability to simulate deformation laws and damage accumulation processes. The research establishes a theoretical framework for analyzing wellbore instability mechanisms in deep coalbed methane reservoirs, providing critical insights for drilling fluid optimization and geomechanically risk mitigation strategies.